Can We Quantify Functional Improvement Following Total Knee Arthroplasty in the Clinical Setting? - Parks, Nancy L.; Whitney, Catherine E.; Engh, Gerard A. (The Journal of Knee Surgery, 2015)
The purpose of this study was to determine if improvements in knee function after arthroplasty could be practicably measured in the clinical setting using available, validated technology. The tools we assessed included a timed test of common activities, a platform posturography analysis, and a portable gait laboratory device to quantify body segment motion. We measured the function of 25 total knee arthroplasty patients before surgery and at 1, 4, 12, and 24 months after surgery. Assessment of sit-to-stand, walking, stair climbing, lunging, Knee Society Scores, and Oxford Survey Scores were collected at each interval. Patients showed significant improvement in step length, gait speed, symmetry of weight distribution, symmetry of lunging, and speed of stair climbing. Changes in function with long-term follow-up can be precisely measured, making this technology promising for clinical or research applications.
Keywords: total knee arthroplasty; functional testing; gait; clinical outcome